(3aJM GdbQjH GdeLjH Ydi GdJQZjH hGdJQgjHs - (3MSf Hf YdjGdajhej GdbGgQj, CHh Ydj,J (B870 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdLeYI hGdJQZjH ai UdGJgG hGdSYi EdjgG Hbhdg (B: (3GdLeYI JbGd HVe Gdeje hEScGfgG haJMgG hKdGK dZGJ McGgf GdhGMOi s
(3BNQgG (B:s
(3gGgfG CTGQ Edi Cf gPg GdjbYI ef GdTGe hde jJYQV Edi CfgG GHJOGA GdTGe ChdG GfJgi cdGe GHf GdCKjQ bGd GdRQcTi s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(138 / 80) s
Keywords: (3GdMOjK h GdeUWdMs